2020
DOI: 10.3341/kjo.2019.0094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Combinations of Maximum Medical Therapy for Lowering Intraocular Pressure in Primary Open-angle Glaucoma

Abstract: We sought to compare the efficacy as well as the safety of two maximum medical therapy combinations applied to lower the intraocular pressure (IOP) in different primary open-angle glaucoma (POAG) age groups. Methods: This was a retrospective, consecutive case series study that included 60 eyes of 60 subjects with POAG, specifically 20 subjects aged 40 to 54 years, 21 aged 55 to 69 years, and 19 aged 70 years or older. All had been treated for at least 12 months with triple maximum medical therapy (TMT; dorzola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
“…No statistically significant difference was found between the double and triple maximum medical therapy groups in terms of IOP reduction rate, but the rate of ocular adverse effects such as conjunctival hyperemia and dry eye was significantly lower in the double maximum therapy group. Similarly, Wy et al 19 examined POAG patients who switched from triple maximum medical therapy (dorzolamide/timolol combination + brimonidine + latanoprost) to double maximum medical therapy (tafluprost/timolol combination + BBFC). Although IOP reduction rates were similar between the double and triple maximal medical therapy groups, the dry eye rate was significantly lower in the double maximal therapy group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concomitant use of two different drugs may lower medication adherence and consequently fail to control IOP [8]. Thus, to reduce the number of drugs a person intake and to improve medication adherence, a fixed-dose combination (FDC) therapy (i.e., two or more drugs contained in a single dosage form), which has advantages in patient convenience, has been developed for glaucoma patients who do not respond to monotherapy [9]. Examples of FDC therapies commonly applied to glaucoma patients include a combination of prostaglandin analogs and beta blockers, combinations of alpha-2 agonists and beta blockers, combinations of carbonic anhydrase inhibitors and beta blockers, combinations of cholinergic agents and beta blockers, and combinations of carbonic anhydrase inhibitors and alpha-2 agonists [7].…”
Section: Introductionmentioning
confidence: 99%